2020
DOI: 10.18421/tem94-48
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Opportunities to Overcome The Impact Of COVID-19 Pandemic on Power Engineering Education

Abstract: The overall objective of this paper is to propose a viable approach to quality Education in Power Engineering during the COVID-19 period. To this end, we base the study on our previous steps in implementing Augmented Reality technology for training future engineers in the field of energy. To cope with the present challenges brought by the COVID-19 pandemic, we analyzed the necessary paradigm shift to maintain the benefits of using Augmented Reality in teaching.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…A slightly bigger problem arises in departments that require manual measurement and connection of electronic or power system solutions [13]. Courses in which the main area of focus was to teach the student to connect electronic circuits and to program microcontrollers have moved to simulation environments where they can work with development platforms such as Arduino or Raspberry Pi.…”
Section: Introductionmentioning
confidence: 99%
“…A slightly bigger problem arises in departments that require manual measurement and connection of electronic or power system solutions [13]. Courses in which the main area of focus was to teach the student to connect electronic circuits and to program microcontrollers have moved to simulation environments where they can work with development platforms such as Arduino or Raspberry Pi.…”
Section: Introductionmentioning
confidence: 99%
“…They also mentioned that classes, seminars can be moved to online mode however researchers can take equipment's to home (when possible) while colleagues can provide remote support to conduct the experiments. Authors in [10] analysed the benefits and proposed the use of augmented reality (AR) in online delivery of power engineering education during pandemic. However, authors in [25] highlighted some key challenges such as the unavailability of internet service, and limited resources accessibility during the COVID-19 outbreak, which is also experienced by many students in Brazil [26].…”
Section: Globally Observed Covid-19 Challenges On Educationmentioning
confidence: 99%
“…The term "work from home or teach from home" has become very familiar in recent times. The education system has suddenly shifted from classic face-to-face teaching philosophy to online or remote or distance learning mode [10]. Although online or distance learning is known to the academic community, however, the biggest challenge for engineering education is to transform all the face-to-face learning activities into online mode.…”
Section: Introductionmentioning
confidence: 99%
“…The research showed that adding online resources has a positive effect on learning outcomes. In another research [15], the authors investigate the use of Augmented Reality (AR) technology for training future engineers in the field of energy. This study analyzes the paradigm shift for its usefulness in teaching, for example in power engineering education to support online teaching during the pandemic.…”
Section: Literature Reviewmentioning
confidence: 99%